2021
DOI: 10.3389/fnmol.2021.715952
|View full text |Cite
|
Sign up to set email alerts
|

Development of Tinnitus and Hyperacusis in a Mouse Model of Tobramycin Cochleotoxicity

Abstract: Aminoglycosides (AG) antibiotics are a common treatment for recurrent infections in cystic fibrosis (CF) patients. AGs are highly ototoxic, resulting in a range of auditory dysfunctions. It was recently shown that the acoustic startle reflex (ASR) can assess behavioral evidence of hyperacusis and tinnitus in an amikacin cochleotoxicity mouse model. The goal of this study was to establish if tobramycin treatment led to similar changes in ASR behavior and to establish whether ebselen can prevent the development … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 99 publications
(173 reference statements)
0
2
0
1
Order By: Relevance
“…To assess temporal auditory processing, giASRs are evaluated (i.e., the subconscious response of an awake behaving animal in response to a startling sound preceded by a silent gap embedded in a noise) (English & Drummond, 2021;Fournier & Hebert, 2016;Ison et al, 1991;Kodsi & Swerdlow, 1995;Lobarinas et al, 2013;Sebo et al, 2020;Shi et al, 2022;Sun et al, 2011;Weible et al, 2020).In line with previous studies, inhibition of the acoustic startle reflex (ASR) is observed in the presence of a silent gap (Fournier & Hebert, 2016Galazyuk & Hebert, 2015;Longenecker et al, 2021;Moreno-Paublete et al, 2017;Weible et al, 2020;Wilson et al, 2019). This inhibition of the ASR is not diminished following noise exposure, calcium channel blockade or combination of both (Fig.…”
Section: L-type Calcium Channel Blockade Does Not Prevent Noise-enhan...mentioning
confidence: 59%
“…To assess temporal auditory processing, giASRs are evaluated (i.e., the subconscious response of an awake behaving animal in response to a startling sound preceded by a silent gap embedded in a noise) (English & Drummond, 2021;Fournier & Hebert, 2016;Ison et al, 1991;Kodsi & Swerdlow, 1995;Lobarinas et al, 2013;Sebo et al, 2020;Shi et al, 2022;Sun et al, 2011;Weible et al, 2020).In line with previous studies, inhibition of the acoustic startle reflex (ASR) is observed in the presence of a silent gap (Fournier & Hebert, 2016Galazyuk & Hebert, 2015;Longenecker et al, 2021;Moreno-Paublete et al, 2017;Weible et al, 2020;Wilson et al, 2019). This inhibition of the ASR is not diminished following noise exposure, calcium channel blockade or combination of both (Fig.…”
Section: L-type Calcium Channel Blockade Does Not Prevent Noise-enhan...mentioning
confidence: 59%
“…Tobramycin, an aminoglycoside, is commonly used long-term to help treat cystic fibrosis-associated pulmonary bacterial infections [106]. Unfortunately, tobramycin is known to induce ototoxicity [107,108]. Gu and colleagues, however, demonstrated that mice co-treated with ebselen are able to alleviate tobramycin-induced ototoxicity of the cochlea and co-treated cochlear explants were observed to have reduced tobramycin-induced hair cell loss [105].…”
Section: Ebselen/spi-1005mentioning
confidence: 99%
“…Borg, 1982;Overbeck und Church, 1992;Popelar et al, 2008;Alvarado et al, 2012;Möhrle et al, 2019;Kiefer et al, 2022;Koch et al, 2022), ( 2) Mäuse (z.B. Henry, 1979;Kujawa und Liberman, 2009;Hickox und Liberman, 2014;Nowotny et al, 2017;Cederroth et al, 2019;Longenecker et al, 2021;Kiefer et al, 2022), (3) Mongolische Wüstenrennmäuse (z.B. Nowotny et al, 2011;Kiefer et al, 2015;Wrobel et al, 2018;Tziridis et al, 2021;Kiefer et al, 2022), (4) Hamster (z.B.…”
Section: Schwellenbestimmungunclassified